Analysis of the Impact of Using a Gamified App for Spanish Spelling Practice in Primary Education - Esteban Vázquez-Cano; Javier Fombona; María Belén Morales-Cevallos; Eloy López-Meneses (Revista Latinoamericana de Tecnología Educativa)
This study evaluates the impact of GAUBI, a gamified app designed for Spanish spelling practice in primary education, using a quasi-experimental pretest-posttest design with 114 fourth-grade students. Participants were divided into three groups: traditional methods (control group), app use in classrooms (experimental group 1), and app use at home (experimental group 2). The app featured levels of arcade, research, and interactive fiction gameplay, scaling cognitive challenges to enhance learning. The intervention spanned three weeks, with participants engaging in structured app-based or traditional spelling exercises. Results showed that the group using the app at home achieved significantly higher spelling accuracy than those using traditional methods or app-only classroom approaches. Statistical analyses confirmed the superior effectiveness of home-based app use. The Binomial Effect Size Display highlighted notable improvements in specific spelling categories, such as complex letter combinations and accent rules. Discussion centered on the benefits of integrating gamification and ubiquitous learning tools in education, emphasizing the app’s adaptability and immediate feedback, which encouraged independent learning and sustained motivation. The study advocates for blending traditional and gamified approaches to foster comprehensive spelling competence, supporting educators with analytics-driven insights. The research underscores the app's potential to address broader curricular goals, including sustainable development objectives.